Relevansi Pokok-Pokok Pemikiran Paulo Freire Dalam Pelaksanaan Kurikulum 2013 - Dewi Rokhmawati, Sinta, Drs. Mulyadi Sri Kamulyani, SH., M.Pd (2017)
This research aims describe the relevancy of Paulo Freire's fundamental thought in implementation of Curriculum 2013 . This study is a qualitative research using library research design. Collecting data in this study is using documentation and literature. Data analysis technique uses content analysis as to know the thinking of Paulo Freire through various treasures in literature. The examination of data validity uses comfirmability techniques (certainty). Based on this research can be concluded that fundamental Paulo Freire's thought, the humanization, awareness, and dialogue have relevancy in the implementation of Curriculum 2013. Three main ideas sustain the process of Problem Posing Education which is an alternative Paulo Freire in the face of banking system. Problem Posing Education have relevance to the curriculum in 2013 because both are positioned students as subjects, so that the relationship between teachers and students are not the subject-object but subjects thus creating active learning that is centered on students (students centered).